Nonpoint Source Phosphorus Trading in the Cherry Creek Reservoir Watershed in Colorado - Earles, T. Andrew; Lorenz, Wayne F; Koger, Wilbur L; Trujillo, Molly Y (Journal of irrigation and drainage engineering, 2008)
The Cherry Creek Reservoir in the Denver Metropolitan area is subject to the Cherry Creek Reservoir Control Regulation (control regulation), which establishes a total maximum annual load for the reservoir of 6,473 kg (14,270 lb) of phosphorus. The load is distributed among phosphorus sources including background, nonpoint, and regulated storm water, municipal and industrial wastewater facilities, individual sewage disposal systems, and industrial sources. As a part of the control regulation, the Cherry Creek Basin Water Quality Authority (CCBWQA) is authorized to implement and maintain a trading program that allows phosphorus trading and the sale of phosphorus (kg/lb) in the Cherry Creek watershed. The trading program allows dischargers seeking new or increased phosphorus waste load allocations to obtain additional kilograms/pounds of phosphorus by constructing nonpoint source projects meeting certain criteria to immobilize phosphorus. This paper provides an overview of the CCBWQA trading program guidelines and describes two Arapahoe County Water and Wastewater Authority (ACWWA) trade credit projects: Lone Tree Creek Pond L-3 and Windmill Creek Pond W-6/W-7. The Pond L-3 and Pond W-6/W-7 projects are unique because they are the first two (and only two to date) projects that have successfully obtained trade ratios and estimated trade credits under the CCBWQA trading program. This paper describes the administrative and technical process for determining trade ratios and estimating trade credits for nonpoint-source-to-point-source phosphorus trades in the Cherry Creek watershed. The process for going from an established trade ratio and estimated trade credits to actual trade credits applied to a point source discharge presents its own set of challenges. Actual trade credits must be demonstrated by monitoring, which can be very expensive. The monitoring results must be reviewed and approved by CCBWQA before trade credits are awarded, and the Colorado Department of Public Health and Environment Water Quality Control Division must amend the facility’s discharge permit before additional phosphorus can be discharged. Therefore, establishing a trade ratio and estimating trade credits for CCBWQA approval of a phosphorus trading project is only the first step in a potentially expensive and time-consuming process for actually discharging additional phosphorus through a nonpoint-source-to-point-source trade in the Cherry Creek watershed.